What influences the infection of COVID-19 in healthcare workers? - Xiaoquan Lai; Qian Zhou; Xinping Zhang; Li Tan (Journal of Infection in Developing Countries)
Introduction: The outbreak of COVID-19 has spread worldwide. The evidence about risk factors of healthcare workers who infected COVID-19 is limited. This study aims to describe characteristics and influencing factors of the COVID-19 infection in healthcare workers.